The Social Support Programme's Role Analysis in Reducing Poverty: A Case Study in Indonesia - Eko Wahyudi Nugrahadi; Firman Saputra; Nabila Rizki Ramadhani; Nazia Safira Lubis (International Review of Social and Cultural Studies, 2025)
This study aims to analyze the effectiveness of social support programmes in reducing poverty in Indonesia through qualitative research methods and literature review. Social support programmes such as the Family Hope Program (Program Keluarga Harapan, PKH), Non-Cash Food Support (Bantuan Pangan Non-Tunai, BPNT), and Direct Cash Support (Bantuan Langsung Tunai, BLT) have been implemented by the government with the goal of improving the welfare of poor families. The data collected comes from official government reports, case studies, and relevant previous research. The analysis results indicate that these programs have successfully improved access to education, healthcare, and income for poor families, although challenges such as inaccuracies in beneficiary data, complex bureaucracy, and the risk of misuse of authority remain. This study recommends several strategies to maximize the effectiveness of social support programs, including improving data accuracy, simplifying bureaucracy, enhancing transparency, and leveraging digital technology. With the implementation of these strategies, it is hoped that social support programs can become more effective and targeted, thereby significantly and sustainably reducing poverty in Indonesia.